1991
DOI: 10.1093/genetics/129.4.1085
|View full text |Cite
|
Sign up to set email alerts
|

Chromosome rearrangement by ectopic recombination in Drosophila melanogaster: genome structure and evolution.

Abstract: Ectopic recombination between interspersed repeat sequences generates chromosomal rearrangements that have a major impact on genome structure. A survey of ectopic recombination in the region flanking the white locus of Drosophila melanogaster identified 25 transposon-mediated rearrangements from four parallel experiments. Eighteen of the 25 were generated from females carrying X chromosomes heterozygous for interspersed repeat sequences. The cytogenetic and molecular analyses of the rearrangements and the pare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
1

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(55 citation statements)
references
References 30 publications
2
52
1
Order By: Relevance
“…One of the ways in which selection can act against TEs is to remove deleterious chromosomal rearrangements caused by non-allelic homologous recombination, also known as ectopic recombination [62,63]. This occurs due to the high sequence similarity between insertions of the same family located across the genome and can lead to large deletions or inversions when the insertions are on the same chromosome.…”
Section: (I) Selection Against Ectopic Recombinationmentioning
confidence: 99%
“…One of the ways in which selection can act against TEs is to remove deleterious chromosomal rearrangements caused by non-allelic homologous recombination, also known as ectopic recombination [62,63]. This occurs due to the high sequence similarity between insertions of the same family located across the genome and can lead to large deletions or inversions when the insertions are on the same chromosome.…”
Section: (I) Selection Against Ectopic Recombinationmentioning
confidence: 99%
“…In Drosophila, diverse experiments from Sturtevant's (1925Sturtevant's ( , 1929 classic Bar duplication studies to the characterization of putative duplications arising in early intralocus recombination studies at white (Green 1959;Judd 1959;Goldberg et al 1983;Davis et al 1987) fostered this hypothesis. Indeed, a systematic study of ectopic exchange indicated that it could be the most common mutation process in female Drosophila (Montgomery et al 1991).…”
Section: The Ectopic Exchange Modelmentioning
confidence: 99%
“…If two DSBs occur on the same chromosome, re-ligation of the DNA molecule via NHEJ can form inversions ( Hefferin and Tomkinson 2005 ), deletions, or inversions flanked by inverted duplications, if the DSBs are staggered cuts ( Ranz et al 2007 ). Additionally, inversions can result from ectopic recombination (Non-Allelic Homologous Recombination, NAHR) between dispersed repeated sequences including transposons ( Delprat et al 2009 ), retrotransposons ( Kupiec and Petes 1988 ), interspersed repeat sequences ( Montgomery et al 1991 ), or interspersed duplications ( Cáceres et al 2007 ). For example, NAHR between pairs of homologous TEs present in opposite orientations at different positions on a chromosome can lead to inversions of the DNA segment between the two TEs ( Delprat et al 2009 ).…”
Section: Discussionmentioning
confidence: 99%